Empirical Study Regarding Perceptions of the IFRS for SMEs in Arad County - Herbei (Moț), Ioana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
IFRS for SMEs is a change among of each entity, leading both to the positive and negative aspects regarding its application. Our study aims to present the perceptions of accounting experts on the application of IFRS for SMEs in Arad County. For the study was used the questionnaire based on resulted the pros and cons of applying standard responses to small and medium-sized entities, considering the law the main reason for applying standard. The Professional accountants believes that rules should have a major impact among listed entities, which leads to benefits and also difficulties. As beneficits we enumerate improving, comparability and transparency of accounting information and as difficulties specify the auditing, the connection accountancy - fiscality and the report cost - benefit, but we cant fail to mention the lack of skilled personnel. Although there are a number of obstacles and costs as regards implementing IFRS for SMEs in Arad, and national level our respondents were equally agree with the application or non-application of this standard. We mention that the application of this standard requires more than a simple exercise because the rules used may have influenced in the content of the financial statements of the entity.